2015
DOI: 10.1021/acs.jpcb.5b00516
|View full text |Cite
|
Sign up to set email alerts
|

A DFT Study of the Extractive Desulfurization Mechanism by [BMIM]+[AlCl4] Ionic Liquid

Abstract: In this work, the interaction nature between [BMIM](+)[AlCl4](-) ionic liquid (IL) and aromatic sulfur compounds (thiophene, benzothiophene, and dibenzothiophene) has been studied by means of density functional theory (M06-2X functional) combined with an implicit solvation model. Although [BMIM](+)[AlCl4](-) is a metal-containing IL, its extractive desulfurization mechanism is different from other metal-containing ILs but similar to non-metal-containing ILs. Important reactions involved in extractive desulfuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 75 publications
0
55
0
Order By: Relevance
“…For EDS, researchers proposed that hydrogen bonding interactions, π‐π interactions, as well as CH‐π interactions were the main interactions in EDS (Figure d). Our previous work have shown that the essence of those interactions probably arise from electrostatic interaction between solvents and aromatic sulfur compounds …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For EDS, researchers proposed that hydrogen bonding interactions, π‐π interactions, as well as CH‐π interactions were the main interactions in EDS (Figure d). Our previous work have shown that the essence of those interactions probably arise from electrostatic interaction between solvents and aromatic sulfur compounds …”
Section: Discussionmentioning
confidence: 99%
“…Generally speaking, the selectivity for sulfur removal may depend on different physical properties of sulfides for different desulfurization methods but not only depend on the electron density of S atom. For example, in ADS and EDS, the mechanisms show that the selectivity may be determined by the properties of whole molecules but not the electron density of S atom . To find out the relationship between physical properties of sulfides and the selectivity, we have systematically explored this issue by using CDFT for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that electrostatic potential (ESP) analysis, as a reflection of electron density, is significant for noncovalent interaction systems. [58][59][60] For noncovalent interaction systems, van der Waals interactions, hydrogen bonding interactions and other interactions may coexist. All of them or just a few kinds of noncovalent interaction may play important roles in the weak interaction for different noncovalent systems.…”
Section: Analysis On the Formation Mechanismmentioning
confidence: 99%
“…All calculations were carried out by the Gaussian 16 program [30]. For IL calculations, Li et al [31] suggested that the density function of the Minnesota family [32] (e.g., M06-2X) with a diffusion function basis set (e.g., 6-311++G(d,p)) might give reasonable results. If dispersion-corrected density functionals (e.g., gd3bj, DFT-D3) were used, more reliable results could be obtained [33].…”
Section: Theoretical Calculationmentioning
confidence: 99%